Determination of Sterilization Quality Priorities Based on Analytical Hierarchy Process in High Temperature Sterilizers - Mochammad Nurudin; Muhamad Haddin (Lembaga Pengembangan Kinerja Dosen, 2026)
The issue of high-temperature sterilizer quality in the central sterile supply department is an important matter. This is due to the quality of sterilization, which affects the number of surgical instruments and items that become damaged and dull when sterilized. The impact is an increase in high-temperature sterilizer malfunctions. The solution is how to ensure the quality of high-temperature sterilizers. This study discusses the determination of sterilization priorities for high-temperature sterilizers with the aim of providing recommendations for usage priorities. The model is determined as a sterilizer test with inputs: temperature, time, and type, with the output in the form of a sterilizer ranking priority. Specified parameters: sterilizer specifications, temperature, sterilizer volume, and sterilization time. The research stages begin with testing conducted on 4 (four) high-temperature sterilizer units, namely Odelga ISO 9001, Tuttnauer Stera 120, MMM selection Lokal, and TRIDENT MEDICAL EA-632. The Analytical Hierarchy Process method is used to determine sterilization quality priorities in high-temperature sterilizers. The research results show that the Analytical Hierarchy Process can be used to determine sterilization quality priorities. This is evidenced by the best recommendation results from the four high-temperature sterilizer brands, which are: first place MMM selection Lokal, second ODELGA ISO 9001, third TRIDENT MEDICAL, and fourth Tuttnauer Stera 120. Three high-temperature sterilizers of the brands (Odelga, Tuttnauer, MMM) have a temperature accuracy within a tolerance of ±2°C, while TRIDENT MEDICAL shows a deviation of +4.1°C. The results indicate that accurate temperature and time, selection of the appropriate type of high-temperature sterilizer, and AHP-based evaluation are effective in determining the priority scale of high-temperature sterilizers to ensure patient safety in hospitals.